2009
DOI: 10.1038/emboj.2009.324
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of transactive response DNA-binding protein (TDP-43) downregulates histone deacetylase 6

Abstract: TDP-43 is an RNA/DNA-binding protein implicated in transcriptional repression and mRNA processing. Inclusions of TDP-43 are hallmarks of frontotemporal dementia and amyotrophic lateral sclerosis. Besides aggregation of TDP-43, loss of nuclear localization is observed in disease. To identify relevant targets of TDP-43, we performed expression profiling. Thereby, histone deacetylase 6 (HDAC6) downregulation was discovered on TDP-43 silencing and confirmed at the mRNA and protein level in human embryonic kidney H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
227
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(248 citation statements)
references
References 53 publications
18
227
0
3
Order By: Relevance
“…The results from Tg mice expressing wild-type human and mouse TDP-43 are consistent with respect to the loss of nuclear TDP-43 but not cytoplasmic mislocalization 1,35,53,54 . In addition to generating aggregation-prone fragments, the cleavage of TDP-43's C-terminal disrupts binding to hnRNP A1, histone deacetylase 6 and fused in sarcoma/translocated in liposarcoma 2,55,56 . How neurons bearing TDP-43 pathology undergo neuronal death remains to be elucidated, but the present results on AR2 and AR2H mice indicate that the motor neurons expressing Q/R site-unedited GluA2 (refs 18, 25) exhibit loss of TDP-43 in the nucleus but not necessarily abnormal cytoplasmic inclusions during the process to death.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…The results from Tg mice expressing wild-type human and mouse TDP-43 are consistent with respect to the loss of nuclear TDP-43 but not cytoplasmic mislocalization 1,35,53,54 . In addition to generating aggregation-prone fragments, the cleavage of TDP-43's C-terminal disrupts binding to hnRNP A1, histone deacetylase 6 and fused in sarcoma/translocated in liposarcoma 2,55,56 . How neurons bearing TDP-43 pathology undergo neuronal death remains to be elucidated, but the present results on AR2 and AR2H mice indicate that the motor neurons expressing Q/R site-unedited GluA2 (refs 18, 25) exhibit loss of TDP-43 in the nucleus but not necessarily abnormal cytoplasmic inclusions during the process to death.…”
Section: )mentioning
confidence: 99%
“…The disease course is rapidly progressive, and the eventual respiratory muscle weakness results in death within a few years of onset. The cause of ALS is largely unknown, but transactive response DNA-binding protein 43 (TDP-43), a nuclear protein involved in the regulation of RNA processing [1][2][3][4][5][6][7] , has recently attracted interest as a molecule relevant to the pathogenesis of this disease. TDP-43 is absent from the nucleus in which it normally resides but localizes in abnormal cytoplasmic inclusions in a considerable proportion of spinal cord motor neurons in the majority of sporadic ALS patients [8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As determined by qRT-PCR, M337V and control iPSC lines expressed similar levels of TARDBP, the pluripotency markers TERT and REX1, and histone deacetylase 6 (HDAC6) mRNA (Fig. 3A), the latter of which is regulated by TDP-43 (30). Western blotting revealed that two independent M337V iPSC clones had higher levels of full-length TDP-43 in the soluble fraction and C-terminal TDP-43 fragments in the detergent-resistant fraction than controls (Fig.…”
Section: M337v Increases Soluble and Detergent-resistant Tdp-43 Proteinmentioning
confidence: 99%
“…To investigate the role of TDP-43 in STS-induced apoptosis in U87, we used TDP-43 siRNA specifically targeted for 3' UTR region of human TDP-43 mRNA (Fiesel et al, 2009) to knockdown endogenous TDP-43 before subjecting to STS (0.5uM) for 40 hours. Immunoblot was performed to exam the knockdown efficiency of siRNA ( Figure 4B).…”
Section: Tdp-43 Knockdown Enhanced Cytotoxicity Of Sts In U87mentioning
confidence: 99%